Pengaruh Penerapan Media Video Animasi Berbasis Powtoon Terhadap Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila di Kelas VIII SMPN 4 Darma - Juliany, Leni; Haerudin, Dodi Ahmad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study was to determine the effect of the application of Powtoon-based animated video media on student learning outcomes in Pancasila Education subjects in class VIII SMP Negeri 4 Darma. The research used a quantitative method with a quasi-experimental design type Nonequivalent Control Group Design, where class VIII A was used as the experimental class and VIII B as the control class. Data collection techniques were carried out through multiple choice tests, documentation, and interviews, with the main instrument being a learning outcome test. Data analysis used Mann-Whitney test and N-Gain test. The results showed that there was no significant effect between the application of Powtoon-based animated video media and student learning outcomes, as indicated by the Asymp.Sig (2-tailed) value of 0.250> 0.05. However, there is an increase in learning outcomes after being given treatment with an average N-Gain value of 0.52451 which is in the moderate category. This shows that even though the research hypothesis is rejected, the use of Powtoon media still has a positive impact on increasing student understanding. Therefore, the results of this study can be used as evaluation and consideration material for teachers to develop digital learning media in Pancasila Education subjects, so that the learning process is more interesting, interactive, and able to encourage increased student learning outcomes in the future